An introduction to international varieties of English - Bauer, Laurie, 1949- (Edinburgh textbooks on the English language., 2002)
This study looks at native speaker varieties of English, considering how and why they differ in terms of their pronunciation, grammar, vocabulary and spelling. It shows how the major varieties of English have developed and why similar causes have given rise to different effects.